Description of Leukocytes of Jambal Siam (Pangasianodon hypophthalmus) Feed Containing Papaya Leaf Solution (Carica papaya L.) Fermented - Dian Puspitowati; Iesje Lukistyowati; Henni Syawal (Jurnal Akuakultur SEBATIN, 2022)
Papaya leaves (Carica papaya L.) contain tannins, alkaloids, flavonoids, terpenoids, saponins, and karpain alkaloids which are antiseptic, anti-inflammatory, antifungal, antibacterial and can be used as immunomodulators that can strengthen the immune system. This study aimed to obtain the best dose of fermented papaya leaf (Carica papaya L.) solution in increasing the non-specific immune response of jambal siam fish by looking at total leukocytes, leukocyte differentiation, phagocytic activity, and survival. The method used is an experimental method using a completely randomized design (CRD) with five levels of treatment, namely (Kn): feeding without being given a fermented papaya leaf solution and without being challenged with A. hydrophila bacteria, (Kp): feeding without being given a leaf solution fermented papaya and challenged with A. hydrophila bacteria, and feed added with fermented papaya leaf solution with doses of P1 (16 ml/kg), P2 (18 ml/kg), P3 (20 ml/kg) and challenged with bacteria A. hydrophila. Fish were reared for 46 days. A. hydrophila challenge test was performed on the 32nd day intramuscularly with a density of 108 CFU/ml as much as 0.1 ml/head. The results showed that fermented papaya leaf solution at a dose of 20 mL/kg of feed was the best dose to increase the non-specific immune response of Jambal Siamese fish with an average total leukocyte of 10.05 x104 cells/mm3, lymphocytes 82.00%, monocytes 4 ,67%, neutrophils 6.67%, platelets 6.67%, phagocytic activity 33.67%, and 96,67% survival